Form Content Synchronization with Special Reference to Beau Grande’s Textuality in Wole Soyinka’s “Telephone Conversation” (Journal of Teaching and Research in English Literature, 2014)
One significant observation of new criticism is the form of a text subsumes the content, i.e. the content is inseparably realised in the textual structure. Such a realization is achieved in Soyinka’s poem, “Telephone Conversation”. This article substantiates such synchronization by applying Beaugrande’s concept of ‘Textuality’. Such rigorous application of a theoretical structure as textuality, brings out the underlying racial discrimination of the text very effectively.De Beaugrande and Dressler (1981) have defined ‘Textuality’ as a set of ‘theoretical units’ which succeed in making connections wherever communication events occur. They have proposed seven standards of textuality – cohesion, coherence, intentionality, acceptability, informativity, situationality and intertextuality. These principles are constitutive principles of textual communication.